Discernment, Unity and Reflexivity of Sense in Aristotle and Merleau-Ponty - García, Esteban Andrés (Pensamiento. Revista de Investigación e Información Filosófica, 2024)
This paper develops a comparative analysis of certain common topics in Aristotle and Merleau-Ponty’s theories of perception. It is argued that, in different ways and discussing in each case with different «intellectualist» philosophies, both theories attribute to sense-perception complex capacities of discrimination, unification and self-awareness without the mediation of intellectual functions. From these common elements it becomes possible to outline a consideration of the sentient body which does not reduce it to its materiality, as well as a conception of a self not restricted to thought.
Keywords: perception; discernment; synaesthesia; reflexivity; Aristotle; Merleau-Ponty